Development and characterization of microsatellite loci for Lindera glauca (Lauraceae)1. (4th November 2016) - Xiong, Biao; Dong, Shubin; Qi, Ji; Zhang, Limei; Ha, Denglong; Ju, Yuxi; Zhang, Zhixiang
Abstract : Premise of the study: Microsatellite primers were developed to investigate population genetic structure in Lindera glauca (Lauraceae). Methods and Results: Twenty‐five microsatellite primers were developed and optimized for L. glauca using Illumina's Solexa sequencing technology. These novel primers were found to be polymorphic in nine wild L. glauca populations with 81 total alleles confirmed and genotyped via capillary gel electrophoresis. The total number of alleles, observed heterozygosity, and expected heterozygosity for each population ranged from one to four, from 0.00 to 0.90, and from 0.00 to 0.79, respectively. In addition, the 25 primers were tested in 10 additional individuals of the related species L. communis, and all but four markers showed good amplification results. Conclusions: This set of microsatellite primers is the first specifically developed for L. glauca and will facilitate studies of genetic diversity and evolution among populations of this species.